Management of moderate and severe traumatic brain injury. (13th April 2019) - Abdelmalik, Peter A.; Draghic, Nicole; Ling, Geoffrey S. F.
Abstract : Traumatic brain injury (TBI) is a common disorder with high morbidity and mortality, accounting for one in every three deaths due to injury. Older adults are especially vulnerable. They have the highest rates of TBI‐related hospitalization and death. There are about 2.5 to 6.5 million US citizens living with TBI‐related disabilities. The cost of care is very high. Aside from prevention, little can be done for the initial primary injury of neurotrauma. The tissue damage incurred directly from the inciting event, for example, a blow to the head or bullet penetration, is largely complete by the time medical care can be instituted. However, this event will give rise to secondary injury, which consists of a cascade of changes on a cellular and molecular level, including cellular swelling, loss of membrane gradients, influx of immune and inflammatory mediators, excitotoxic transmitter release, and changes in calcium dynamics. Clinicians can intercede with interventions to improve outcome in the mitigating secondary injury. The fundamental concepts in critical care management of moderate and severe TBI focus on alleviating intracranial pressure and avoiding hypotension and hypoxia. In addition to these important considerations, mechanical ventilation, appropriate transfusion of blood products, management of paroxysmal sympathetic hyperactivity, using nutrition as a therapy, and, of course, venous thromboembolism and seizure prevention are all essential in the management of moderate to severe TBI patients. These concepts will be reviewed using the recent 2016 Brain Trauma Foundation Guidelines to discuss best practices and identify future research priorities.